Recyclable solid-supported catalysts for quaternary ammonium iodide-catalyzed living radical polymerization - Wang, Chen Gang (2020)
Quaternary ammonium iodide (R4N+I-) catalysts immobilized on silica particles, Fe3O4 magnetic particles, and organic resin particles were developed for organocatalyzed living radical polymerization. A random copolymer containing the catalytic R4N+I- moieties and the anchoring triethoxysilyl moieties was synthesized and immobilized onto silica and Fe3O4 particles to give the silica particle- and Fe3O4 particle-supported R4N+I- catalysts. A tertiary-amine-containing polymer resin particle was quaternized to give the resin particle-supported R4N+I- catalyst. The supported catalysts were successfully used to synthesize homopolymers and block copolymers of methyl methacrylate, functional methacrylates, styrene, and acrylonitrile with low dispersities. The supported catalysts were able to be separated (recovered) from the polymerization solutions in simple manners, that is, with centrifugation or with a magnet. The catalysts were reused in five polymerization cycles without a noticeable decrease in the catalytic efficiency. The facile preparation of the supported catalysts, the broad monomer scope, and the feasibility of the catalyst reuse and recycle are attractive features.